Diversity and inclusion matters : tactics and tools to inspire equity and game-changing performance - Thompson, Jason (Professor) (Wiley, 2022)
"Diversity, equity, and inclusion has been a hot topic especially in the tech industry. "Between 2017 and 2018, postings for diversity and inclusion positions had increased by nearly 20%--and that number is growing." Many companies are struggling to achieve their DEI goals and develop successful programs. Thompson addresses one of the major issues: there is no handbook that helps people develop and create an effective DEI program. Most work is currently being done on ROI, what diversity means, and how to define it, but there are not books that help you develop an actual program. Thompson provides diversity officers with a blueprint, information, and tools to implement a successful diversity program. Thompson's insights can jumpstart and hep implement a diversity program that can gain immediate traction. He walks you through the process of execution on a weekly and even daily basis. His book shares practical, concrete steps about what data to collect and how to analyze and assess that data, choose the right diversity goal given your current resources, and how to measure the impact of your DEI efforts. He shares practical step-by-step lessons learned, the order you should build your program, and what things you should be working on. You can implement a program in which there previously was no roadmap. You will learn: How to build a successful diversity program with step-by-step instructions How to manage and lead a diversity council How to not just develop programs but understand the order they should be built to insure success How to get early buy-in and long-term commitments from CEOs by knowing when to push and what to ask for How to set appropriate expectations from a DEI program for the CEO and the executive leadership team How to understand your company How to build a plan and program that is tailored to your company and its culture How to set the right DEI goals, collect the right data, and measure your success How to know the difference between a program that is failing and one that is taking awhile to get going"--